Power and Influence of Economists Contributions to the Social Studies of Economics - Maesse, Jens; Pühringer, Stephan; Rossier, Thierry; Benz, Pierre (Routledge Frontiers of Political Economy, 2022)
Economists occupy leading positions in many different sectors including central and private banks, multinational corporations, the state and the media, as well as serving as policy consultants on everything from health to the environment and security. Power and Influence of Economists explores the interconnected relationship between power, knowledge and influence which has led economics to be both a source and beneficiary of widespread power and influence. The contributors to this book explore the complex and diverse methods and channels that economists have used to exert and expand their influence from different disciplinary and national perspectives. Four different analytical views on the role of power and economics are taken: first, the role of economic expert discourses as power devices for the formation of influential expertise; second, the logics and modalities of governmentality that produce power/knowledge apparatuses between science and society; third, economists as involved in networks between academia, politics and the media; and forth, economics considered as a social field, including questions of legitimacy and unequal relations between economists based on the detention of various capitals. The volume includes case studies on a variety of national configurations of economics, such as the US, Germany, Italy, Switzerland, Greece, Mexico and Brazil, as well as international spaces and organisations such as the IMF. This book provides innovative research perspectives for students and scholars of heterodox economics, cultural political economy, sociology of professions, network studies, and the social studies of power, discourse and knowledge.